THE USE OF EDUCATIONAL TECHNOLOGY IN THE DESIGN OF LESSONS: PROBLEMS AND SOLUTIONS - Professor Zakirova F. M.; D. Karshiyeva (International Journal of Innovations in Engineering Research and Technology, 2021)
In this article we will talk about the “quest” technology in the planning, design of the school lessons, its features, types and problems and solutions of their application in education.